PERANAN USAHA KECIL DAN MENENGAH DALAM PENYERAPAN TENAGA KERJA DAN TINGKAT PENDAPATAN MASYARAKAT MISKIN DI KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Wenagama, I Wayan (Buletin Studi Ekonomi; Vol 18, No. 1,Februari 2013. (PP 1-84), 2013)
This research studied poor households who work in SMEs in Abiansemal District – Badung Regency. 18 villages (90 respondents) are choosed by using simple random sampling with Frank Lynnch formula. Analysis used in this research was descriptive comparatif. The results showed that most respondent’s education level was elementary school and the lowest was vocational school The amount of labour were absorbed mostly in the agricultural sector by 30 respondents which was followed from the construction workers by 17 respondents from trade sector and wood craftsmen each 10 respondents,the lowest was the store buildings on labuor, labour tractors and craft workers cloves each 1 respondent . SMEs only absorbed 50 respondents (55.56%). Respondents who used the full time works was 78 respondents Respondents who receive above the minimum wage were 26 respondents   and those earning below the minimum wage were 64 respondents
Keywords: SMEs and poverty